Pengaruh Gaya Kepemimpinan, Komunikasi dan Lingkungan Kerja Fisik Terhadap Semangat Kerja Karyawan pada PT. BPR TISH Sukawati Gianyar - Paryudi, Made; Ardana, I Komang (E-Jurnal Manajemen; Vol 3 No 1 (2014), 2014)
This study was aimed to investigate the effect of partially simultaneously and leadership styles, communication and physical work environment for employee morale at PT. BPR Tish Sukawati Gianyar and to determine which variables are dominant influence on employee morale. Sampling technique used is the census method with a sample size of 46 people. Observation, interviews and questionnaires were used in data collection methods. Analysis using multiple linear regression techniques. The result showed that the style of leadership, communication and physical work environment has the effect of simultaneously or partially on the morale of employees at PT. BPR Tish Sukawati Gianyar. While the variables that have a dominant influence on employee morale at PT. BPR Tish Sukawati Gianyar is variable leadership style. Related to research findings that leadership style became dominant variables that have an influence, it may be advisable for the company to pay attention to his leadership style, to be able to provide the motivation to move forward and satisfaction in the work, so that the spirit and excitement of the work can be improved. Keywords : leadership styles, communication, physical work environment, employee morale